Upaya Meningkatkan Hasil Belajar Siswa melalui Media Kosa Kata Bergambar Pada Pelajaran Bahasa Arab Kelas V MI Birrul Walidain NW 2 Rensing: Efforts to Improve Student Learning Outcomes Through Illustrated Vocabulary Media in Arabic Language Lessons for Class V MI Birrul Walidain NW 2 Rensing - Nasrullah (Al-Faiza : Journal of Islamic Education Studies, 2025)
Arabic is one of the subjects that must be present in every level of education. Because mastery of Arabic is an important requirement for the success of individuals, the people of the Indonesian nation in responding to the challenges of the times at the global level. This research was 1) To find out efforts to improve the learning outcomes of class V students in Arabic language lessons on Islamic language material at MI Birrul Walidain NW 2 Rensing 2) to determine the improvement in learning outcomes of class V students in Arabic language lessons on Islamic language material الجسم اعضاء MI Birrul Walidain NW 2 Rensing. The method that researchers use in this classroom action research is the Kurt Lewin model in which there are 4 (four) stages, namely planning, action, observation and reflection. The subjects in this research were class V students at MI Birrul Walidain NW 2 Rensing, consisting of 12 students. The results of the research show that the use of pictorial vocabulary learning media in improving the learning outcomes of class V students at MI Birrul Walidain NW 2 Rensing can be said to be successful because it has increased in the learning process and is the right media to overcome the problems described in the background. This can be proven by the average student score in each cycle increasing, namely in the pre-cycle the average student score was 69.41 (fair category), in cycle I the average student score was 76 (good category), and in cycle II the students' average score was 84 (good category).